Effect of led light on postharvest photosynthesis of Asparagus officinalis l. "Asparagus" - Chicama-Palacin, Solmaira (2024)
Peru is the second largest producer of asparagus, with a production of more than 366 thousand tons per year, its crops are developed mainly in La Libertad, Ica and Lima, its export is mainly to the United States, and in some European countries, also distributed to the domestic market, but during transport and storage problems have been identified that accelerates the expiration of asparagus to increase its high respiratory rate. Therefore, new methods are sought to preserve and delay the senescence of green asparagus, and the following objective of the light emitting diode (LED) that has effect on the photosynthesis of green asparagus Asparagus officinalis L. in the postharvest and if it would serve as a method of conservation. For the realization of this work, four experiments were carried out: A control group kept in total darkness and three other experimental groups that were exposed to different power 7 W, 15 W and 20 W, respectively, exposed to 14 h of light and 10 h of darkness, using the photosynthetic quantification method through the extraction of chlorophyll to find the amount of chlorophyll a, b and total chlorophyll, The result was that the experimental group exposed to a power of 20 watts has a difference of 40% of chlorophyll compared to the control group, this shows that the high power white LED light prevents a greater degradation of the total chlorophyll of green asparagus, giving a commercial shelf life of three days at room temperature.